Evaluation de l’effet bioinsecticide des extraits des feuilles de Pinus pinaster et de Rosa sp sur le puceron vert du rosier (Macrosiphum rosae) et la punaise du tilleul (Oxycarenus lavaterae "Fabricius,1787") . - BENCHENDIKH, Sara; BELAROUCI, Nour El Houda (My University, 2025)
This research is part of a biological control approach by testing the bioinsecticide effect of hydroethanolic extracts of dry leaves from two plant species: Pinus pinaster (maritime pine) and Rosa sp. (rose), targeting horticultural crop pests, notably the green rose aphid (Macrosiphum rosae) and the linden bug (Oxycarenus lavaterae). Fresh leaves of Rosa sp. and Pinus pinaster are characterized by a moisture content of 64% and 44% and extraction yields of 66.8% and 65.6%, respectively. The Rosa sp. extract causes almost total mortality in Macrosiphum rosae and 50% mortality in Oxycarenus lavaterae, at a 100% dose and after 1 hour of treatment exposure. After 72 hours, and for both insects, doses of 20% and 100% resulted in mortality exceeding 80% and 100%, respectively. Application of Pinus pinaster extract induced 100% total mortality, under the effect of the 100% dose and after 1 hour of treatment exposure, in both insects tested. While the 20% dose showed very high efficacy after 72 hours, where total mortality (100%) was recorded in both insects tested. The LD50 values confirm these results. The bioinsecticide effect of both extracts is mainly due to the richness of phytochemical components already tested in this study (alkaloids, flavonoids, tannins, quinones, saponins, terpenoids, reducing compounds, mucilages).
Keywords: Hydroethanolic extract, Pinus pinaster, Rosa sp, Oxycarenus lavaterae, Macrosiphum rosae, bionsecticide